Profiling Proteins in the Hypothalamus and Hippocampus of a Rat Model of Premenstrual Syndrome Irritability - Mingqi Qiao; Peng Sun; Yang Wang; Sheng Wei; Xia Wei; Chunhong Song; Fushun Wang; Jibiao Wu (Neural Plasticity)
Premenstrual syndrome (PMS) refers to several physical and mental symptoms (such as irritability) commonly encountered in clinical gynaecology. The incidence of PMS has been increasing, attracting greater attention from medical fields. However, PMS pathogenesis remains unclear. This study employed two-dimensional gel electrophoresis (2DE) for proteomic map analysis of the hypothalamus and hippocampus of rat models of premenstrual syndrome (PMS) irritability. Matrix-assisted laser desorption/ionisation time of flight mass spectroscopy (MALDI-TOF-MS) was used to identify proteins possibly related with PMS irritability. Baixiangdan, a traditional Chinese medicine effective against PMS irritability, was used in the rat model to study putative target proteins of this medicine. The hypothalamus and hippocampus of each group modelling PMS displayed the following features: decreased expression of Ulip2, tubulin beta chain 15, α actin, and interleukin 1 receptor accessory protein; increased expression of kappa-B motif-binding phosphoprotein; decreased expression of hydrolase at the end of ubiquitin carboxy, albumin, and aldolase protein; and increased expression of M2 pyruvate kinase, panthenol-cytochrome C reductase core protein I, and calcium-binding protein. Contrasting with previous studies, the current study identified new proteins related to PMS irritability. Our findings contribute to understanding the pathogenesis of PMS irritability and could provide a reference point for further studies.